Kajian Kadar Batas Optimum (Orytimum Cut-off Grade) pada Penambangan Nikel Laterit dengan Penjualan dalam Bentuk Material Bijih Mentah - , Wahyu Sasongko ([Yogyakarta] : Fakultas Teknik UGM, 2013)
Optimum cut-off grade (COG) is approached by 112 degree equation of A component divided by B component. A component is defined as variable costs appeared along nickel mining chain and fixed costs, whereas B component is acted as production dues, nickel ore prices in global market, characteristic constant of processing recovery, water content ofnickel ore and mining recovery factors. To achieve a low optimum COG, a strategy on A component is needed including (1) well-define the mining chain skucture to define activity and corresponding costs, and (2) carry out a cost ef{iciency and mining effectiveness. In order to attain a low optimum COG, the significant and sensitive aspects of B component are important to be taken into account including nickel price and water content of nickel ore. Traditionally, the optimum COG without considering interest rate (r) and optimization factors is called as break even cut-off grade abbreviated as BECOG. For a further study, an optimum COG by considering interest rate (r) and optimization factors is absolutely needed to be incorporated. A development of this research should be directed to the implementation of Government Regulation (PP) No. 7, 2012 about added value of processing and smelting of ore minerals, where in Article 4 it is stated that the ore mining company has an obligatory to carry out a processing and smelting at a minimum limit. Build up owrl processing plant or selling nickel ore for domestic market need a careful study on optimum COG, reserves optimization and mining design as well as taking strategic decision both from govemment and/or mining company management. Keywords: Optimum cut-off grade, mining and lateritic nickel ore